2023
DOI: 10.3390/molecules28145431
|View full text |Cite
|
Sign up to set email alerts
|

Faba Bean Processing: Thermal and Non-Thermal Processing on Chemical, Antinutritional Factors, and Pharmacological Properties

Abstract: The food industry, academia, food technologists, and consumers have become more interested in using faba bean seeds in the formulation of new products because of their nutritional content, accessibility, low costs, environmental advantages, and beneficial impacts on health. In this review, a systematic and up-to-date report on faba bean seeds’ antinutrients and bioactive and processing techniques is comprehensively presented. The chemical composition, including the oil composition and carbohydrate constituents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 145 publications
0
3
0
Order By: Relevance
“…A reduction in the ANFs in grain legumes as a result of the extrusion process is evidenced in several research studies [58,183,252,297,298]. Alonso et al [252] reported reductions in the contents of number of ANFs (condensed tannin, trypsin, chymotrypsin, α-amylase inhibitors and haemagglutinating activity) in field peas as a result of extrusion at 148 • C, 25% moisture and 100 rpm.…”
Section: Thermal Processing Of Grain Legumesmentioning
confidence: 98%
“…A reduction in the ANFs in grain legumes as a result of the extrusion process is evidenced in several research studies [58,183,252,297,298]. Alonso et al [252] reported reductions in the contents of number of ANFs (condensed tannin, trypsin, chymotrypsin, α-amylase inhibitors and haemagglutinating activity) in field peas as a result of extrusion at 148 • C, 25% moisture and 100 rpm.…”
Section: Thermal Processing Of Grain Legumesmentioning
confidence: 98%
“…Faba bean (Vicia faba L.) belongs to the Fabaceae family and stands as the globe's ancient crop cultivated plants, it is native to Mediterranean countries. It is used to prepare different dishes due to its edible seeds (Çilesiz et al, 2023), it provides an essential source of protein, starch, fiber, vitamins, and minerals (Badjona et al, 2023). Faba bean has also a high potential to promote human health as well as prevent obesity and diseases such as cholesterol, glycemic, coronary heart diseases, and colon cancer (Steen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Faba bean has also a high potential to promote human health as well as prevent obesity and diseases such as cholesterol, glycemic, coronary heart diseases, and colon cancer (Steen et al, 2010). Additionally, this species exhibits high antioxidant and anti-inflammatory effects (Badjona et al, 2023).…”
Section: Introductionmentioning
confidence: 99%